Revisiting autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) mutations in the nicotinic acetylcholine receptor reveal an increase in efficacy regardless of stochiometry. (January 2019) - Indurthi, Dinesh C.; Qudah, Taima; Liao, Vivian W.; Ahring, Philip K.; Lewis, Trevor M.; Balle, Thomas; Chebib, Mary; Absalom, Nathan L.
Graphical abstract: Abstract: Autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) is a genetic form of epilepsy that is caused by mutations in several genes, including genes encoding for the α4 and β2 subunits of the nicotinic acetylcholine (nACh) receptor. Pentameric α4β2 nACh receptors are the most abundant nicotinic receptor in the mammalian brain and form two stoichiometries, the (α4)3 (β2)2 and (α4)2 (β2)3 receptors that differ in their physiological and pharmacological properties. The purpose of this study was to investigate how ADNFLE mutations β2 V287M, β2 V287L or α 4T293I manifest themselves in different receptor stoichiometries. We expressed wild-type and mutant receptors in Xenopus oocytes and measured the response to ACh and other agonists at both receptor stoichiometries. For all three mutations, the efficacy of ACh at (α4)2 (β2)3 receptors was increased. At (α4)3 (β2)2 receptors, the efficacy of activation was increased both when two molecules of agonist, either ACh or the site-selective agonist sazetidine-A, were bound at the α4-β2 interfaces, and when a third ACh molecule was bound at the α4-α4 site. Regardless of stoichiometry, the mutations increased the current elicited by low concentrations of ACh. Further, the smoking cessation agents, nicotine, varenicline and cytisine increased activation of mutant (α4)3 (β2)2 receptors, while only nicotine increased activation of mutant (α4)2 (β2)3 receptors. Chronic exposure of all agonists reduced ACh-activation levels at low and high ACh concentrations. From this, we concluded that mutations that cause ADNFLE manifest themselves in a change in efficacy regardless of the stoichiometry of the receptor.